Geography of Gender Inequality in Mexico - Díaz Barajas, Yesica; Zamora Torres, América Ivonne (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2024)
Gender inequality in Mexico is still an obstacle for the female population to reach their maximum human potential in accordance with the advances in the development of the regions, so that the studies that pay to quantify it, represent important analysis tools to incorporate and prioritize different gender issues on the public agenda. The document addresses the theoretical and referential context of gender inequality, prioritizing the dimensions of reproductive health, empowerment and work. The aim of this work is to identify the geographical structure of inequality in our country, through a k-means cluster analysis, based on the Expanded Gender Inequality Index (IDGA) calculated for the states of Mexico in 2020, which allows finding the convergences and divergences in gender inequality in the three dimensions included in the index, grouping the entities according to their similarity in the degree of progress towards equality: leaders, followers and laggards. In the results of the study, it stands out that, in the general progress towards gender equality, five entities make up the cluster of leaders, with IDGA values less than 0.337; fifteen entities belong to the cluster of followers, with values between 0.386 and 0.430; and twelve entities make up the cluster of laggards, with values greater than 0.431; the state of Chiapas coinciding in the cluster of laggards in all three dimensions.
Keywords: women; gender inequality; human development; clusters; public policies